Serum 25‐Hydroxyvitamin D Levels and Survival Outcomes in Advanced Biliary Tract Cancer: Results From the NIFTY Trial - So Heun Lee; Jaekyung Cheon; Ilhwan Kim; Kyu‐pyo Kim; Baek‐Yeol Ryoo; Jae Ho Jeong; Myoung Joo Kang; Byung Woog Kang; Hyewon Ryu; Ji Sung Lee; Changhoon Yoo (Cancer Medicine)
ABSTRACT Background Numerous studies have explored the role of vitamin D in various cancers; however, its impact on advanced biliary tract cancers (BTC) within a prospective cohort remains to be investigated. This preplanned subgroup analysis of the NIFTY trial evaluated the prognostic implications of serum vitamin D levels in patients with advanced BTC undergoing second‐line chemotherapy. Methods From the 174 patients in the NIFTY trial, a total of 173 patients (99.4%) were included in this analysis comparing a liposomal irinotecan plus 5‐FU/leucovorin group (n = 87) and a 5‐FU/leucovorin alone group (n = 86). Baseline serum 25‐hydroxyvitamin D (25(OH)D) levels, an indicator of vitamin D status, were analyzed for their association with baseline characteristics and overall survival (OS) in patients undergoing second‐line chemotherapy. Multivariable Cox proportional hazards regression and a restricted cubic spline function were used to assess the association with OS. Results There were no significant associations between baseline characteristics and serum 25(OH)D levels. Baseline serum 25(OH)D levels were not associated with OS in either the multivariable Cox proportional hazard regression or restricted cubic spline analysis. In the subgroup analysis, however, higher serum 25(OH)D levels were significantly associated with poorer OS in female patients, while no significant association was observed in male patients, indicating a significant interaction by sex. Additionally, a marginally significant interaction was observed between body mass index and serum 25(OH)D levels for OS, with higher levels associated with better OS in patients who were underweight. Conclusions Our preplanned subgroup analysis of the NIFTY trial indicates that the serum 25(OH)D levels did not have a significant effect on OS in the overall patient population with advanced BTC. However, higher serum 25(OH)D levels were associated with worse OS in female patients, underscoring the need for further investigation into the role of vitamin D in BTC.